Developing and applying tools for experimental economic research: social cohesion, other-regarding preferences & creativity - Baader, Malte (2022)
This thesis contributes to the evaluation and development of experimental methodologies within experimental economics. Across two parts and five chapters, I outline three novel experimental instruments to measure social cohesion, distributional preferences and creativity. First, I provide a general introduction that gives an overview of the main topic of the thesis and summarises each chapter. The focus of Part I is social cohesion and distributional preferences. In Chapter 1, we propose a condensed version of a prominent methodology to estimate distributional preferences based on allocation decisions in repeated dictator games (Fisman et al., 2007). We show that we can reduce the total number of decisions by 60% whilst maintaining high accuracy in the estimation of distributional preference parameters. The developed methodology successfully reduces cognitive subject burden and shortens elicitation time by 50%, therefore substantially improving the efficiency of the original instrument. In Chapter 2, we develop a more nuanced version of the ‘Inclusion of Others in Self’ (IOS) scale, an established methodology to measure social cohesion. By extending the answer range and creating a computerised interface, we are able to increase measurement accuracy whilst simplifying the experimental implementation. Moreover, we also conduct a detailed replication of Gächter et al. (2015) supporting the robustness of our proposed tool. In Chapter 3, finally, we apply both instruments developed in Chapter 1 and 2 by investigating the relationship between social cohesion, distributional preferences and altruistic giving in a network of university students. We find that social cohesion significantly affects altruistic giving with distributional preferences serving as a fundamental mediating factor. Shifting the thesis’ focus, Part II explores topics related to experimental creativity research. In Chapter 4, we compare five experimental creativity tasks across two studies in a withinsubject design. We find no evidence that the examined creativity tasks elicit a common underlying creative ability. Moreover, across both studies there is no relationship between survey measures of creativity and performance in experimental tasks. Chapter 5 builds on these results by proposing a novel creativity task, focusing on creative associative thinking and substantially improving experimental properties. Our proposed method elicits two types of associative thinking that we benchmark against two established creativity tasks. We find that performance in our proposed tasks significantly correlates to their established counterpart, while behaviour in the tasks as well as incentive effects differ between the two types of associative thinking. Finally, Part II concludes with a brief summary of the previous chapters and discusses potential applications of our developed creativity tasks for future research.